Analisis Konflik Isu LGBT di Indonesia Perspektif Dakwah Persuasif - Syaiful Yahya, Mustafa Kharis; Ahmad, Farhan Ansharullah; Hanifah, Najmy; Nurdin, Ali (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
This study analyzes conflicts related to Lesbian, Gay, Bisexual and Transgender (LGBT) issues in Indonesia through the perspective of persuasive da'wah. This study aims to understand how conflicts around LGBT emerge, develop and are managed, as well as to formulate effective da'wah strategies in creating an inclusive dialogue between religious values and individual freedom. The methodology used is a descriptive qualitative approach with media text analysis. The findings show that a persuasive da'wah approach based on dialogue, empathy and education can reduce stigma against the LGBT community. This approach creates a new understanding of the role of da'wah in addressing value and identity-based conflicts in Indonesia's plural society. This research offers insights for preachers to develop more adaptive and compassionate communication strategies, with the aim of achieving greater social harmony.